PERANCANGAN SISTEM PEMINJAMAN BARANG INVENTARIS BERBASIS WEB DI SMPN 2 KUTAWALUYA - Dewi Jayanti, Titi; Abu Bakar Sidik, Haris; Yulia Putri, Sumaya (INFOKOM (Informatika & Komputer), 2024)
Loan data of inventory items if not done properly and correctly then loss of goods can occur due to negligence in data collection that is not neat so that it is not controlled and not properly archived. The author aims to help overcome the risk of undesirable things happening and data archives being erased, Make it easy to present reports so that they can be generated automatically so that teachers, employees or borrowers can easily apply for borrowing inventory items online, Make it easy for administrative staff to make borrowing data inventory items by staff and teachers at SMPN 2 Kutawaluya. The system design method used in this research is the waterfall method. The system modeling uses Symbol Diagrams, Entity Relationship Diagrams and Usecase diagrams. The design of this inventory loan system was built using MySQL. The results of this Inventory Loan System Design are expected to make it easier to input data and the process of borrowing inventory items that were previously done manually in the form of letters with Microsoft Word can now improve data security and can make it easier for staff to make inventory loan reports that can be made automatically.